1998
DOI: 10.1002/(sici)1096-8628(19980806)78:5<474::aid-ajmg14>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence that the Hajdu-Cheney syndrome and the ?serpentine fibula-polycystic kidney syndrome? are a single entity

Abstract: The Hajdu-Cheney syndrome (HCS) is a rare autosomal dominant disorder. It comprises a coarse face, short neck, hirsutism, joint laxity, and normal intelligence. Bone dysplasias, include acro-osteolysis, bathrocephaly, and vertebral anomalies. In 1988, Exner [1988: Eur J Pediatr 147:544-546] coined the term "serpentine fibula-polycystic kidney syndrome" (SFPKS) when he reported on a girl with short stature, unusual facial appearance, polycystic kidneys, and elongated curved fibulae. He postulated that it was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 35 publications
2
15
1
Order By: Relevance
“…Postmortem autopsy, radiographs and histology suggested SFPKS. Previous reports have noted the phenotypic similarities between SFPKS and HCS [Kaplan et al, ; Fryns et al, ; Ramos et al, ]. Phenotypic comparisons between AGS, HCS, SFPKS and this case are illustrated in Table and as listed in the table, the abnormalities identified in the case are characteristic for the NOTCH2 spectrum of disease.…”
Section: Discussionsupporting
confidence: 51%
“…Postmortem autopsy, radiographs and histology suggested SFPKS. Previous reports have noted the phenotypic similarities between SFPKS and HCS [Kaplan et al, ; Fryns et al, ; Ramos et al, ]. Phenotypic comparisons between AGS, HCS, SFPKS and this case are illustrated in Table and as listed in the table, the abnormalities identified in the case are characteristic for the NOTCH2 spectrum of disease.…”
Section: Discussionsupporting
confidence: 51%
“…Previously the delineation of these two disorders has primarily been through the presence of serpentine fibulae in SFPKS, while individuals with HCS have acroosteolysis and coarse hirsute facial features. However, both conditions have cystic renal disease as a phenotypic feature and serpentine fibulae have also been documented in HCS cases 8,11 casting doubt on these conditions being distinct. Case one 5 was originally reported as an example of familial SFPKS, but her phenotype has evolved into a more typical HCS presentation complete with acrosteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Broad phenotypic similarities have been observed between MNS, HCS and SFPKS (Table 1; Majewski et al, 1993;Hamel et al, 1995;Kaplan et al, 1995;Ramos et al, 1998;Brennan and Pauli, 2001). Prominent eyes, full cheeks, dental anomalies, micrognathia, bowed bones, vertebral anomalies and congenital heart disease have been reported in all three of these disorders.…”
Section: Discussionmentioning
confidence: 80%
“…Fryns et al (1997) reported a 36-year-old HCS patient with cystic kidney disease, also prompting the conclusion that HCS and SFPKS are variants of the same disease. After revision of the reported patients in the literature, Ramos et al (1998) concluded that both conditions represent a single entity with a variable degree of expression.…”
Section: Discussionmentioning
confidence: 99%